Voluntrip atau Voluntrap? Mengungkap Permasalahan Etis dalam Voluntourism for Profit: Studi Kasus Project Bakti Milenial #6 Banda Neira - Nisa, An Nuur Khairune; Fadin, Delfyan Intan Nurmala (Gadjah Mada Journal of Tourism Studies, 2024)
This study examined the ethical concerns related to profit-driven voluntourism, specifically highlighting Project Bakti Millenial #6 in Banda Neira. The study sought to elucidate the ethical issues and obstacles inherent in voluntourism, emphasizing the intricacies of merging voluntary activity with commercially-driven tourism activities, which was termed a 'voluntrap'. This study offered a comprehensive examination of the ethical implications and repercussions of such programs and delivered a critical analysis of Project Bakti Millenial #6 as a case study. This research revealed that the complexities stemming from the commercialization of voluntourism underscore ethical concerns, including deceptive claims, information manipulation, and business practices that commodify social activities, thereby necessitating a heightened sense of responsibility in fulfilling the altruistic objectives of voluntourism. Organizing voluntourism necessitates the active involvement of local communities, financial transparency, ethical education, partnership with qualified entities, and enhanced communication to assure sustainability, foster trust, and prevent future issues.